The association of rs4696480 polymorphism in TLR2 gene and Staphylococcus aureus skin colonization in children with atopic dermatitis - O.V. Mozyrska (Group of Companies Med Expert, LLC, 2022)
Topicality. Up to 90% of patients with atopic dermatitis are colonized with S. aureus, with S. aureus predominance being unique to atopic dermatitis. TLR2 play a role in the presentation of S. aureus antigens in a course of atopic dermatits. Purpose - to investigate the association of rs4696480 polymorphism in TLR2 gene and S. aureus skin colonization. Materials and methods. The study included 101 patients with eczema and 84 healthy children. Skin swab cultures were taken. Subjects were classified as carriers if the cultures were positive, while those with culture found to be negative were classified as non-carriers. Genotyping for TLR2 rs4696480 was performed by using Real-time PCR. Results. We determined the prevalence of S. aureus carriage in a cohort study of atopic dermatitis patients in Ukraine. Skin culture for the presence of S. aureus was performed in 82 patients: 45.1% children had positive culture for S. aureus, 54.9% had a negative result. SCORing Atopic Dermatitis (SCORAD) index was significantly higher in S. aureus carriers (p<0.001). There was no difference in genotype distribution among patients and control group (OR=1.021 (95% CI 0.507-2.054) for AT genotype, OR=0.880 (95% CI 0.398-1.947) for TT genotype, р>0.05). AA genotype was significantly more frequent among S. aureus carriers (OR=2.745 (95% CI 0.865-8.708) for AT genotype, OR=7.000 (95% CI 1.852-26.462) for TT genotype. To our knowledge, the association of T16934A (rs4696480) and S. aureus colonization of lesion skin in children with atopic dermatitis have not been studied before. Conclusions. AA variant of TLR2 rs4696480 polymorphism predisposes to S. aureus colonization of skin in children with atopic dermatits. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of the participating institution. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the author.